Not useful to inform teaching practice? Student teachers hold skeptical beliefs about evidence from education science - Voss, Thamar (Frontiers in Education, 2022)
A goal of teacher education is to promote evidence-based teaching. Teacher beliefs are assumed to act as facilitators or barriers to evidence-based thinking and practices (Fischer, 2021). In three sub-studies with a total of N = 346 German student teachers, the extent of student teachers’ beliefs about education science and their consequences and sources were investigated. First, the results of questionnaire data indicated that student teachers held skeptical beliefs about education science: On average, they perceived education science as less complex than their subject disciplines and as less important for successful teaching than their subject didactics. Additionally, they endorsed myths about learning and teaching. Second, the more skeptical the student teachers’ beliefs, the lower their engagement in education science courses within teacher education. Third, hypotheses about potential sources of these skeptical beliefs were experimentally tested as starting points for changing beliefs. The results showed that the ‘soft’ research methods typical of education science and a general tendency to perceive research findings as trivial (hindsight bias) might contribute to this devaluation. Furthermore, students studying the natural sciences and students with little experience with education science held more skeptical beliefs.